Built to fight: variable loading conditions and stress distribution in stag beetle jaws. (2nd July 2015) - Goyens, Jana; Dirckx, Joris; Aerts, Peter
Abstract: Designing very robust structures in an efficient way is a reoccurring challenge in engineering. For male stag beetle weaponry, the solution to this problem was evolved by natural and sexual selection. Stag beetle armature is adapted to perform under extreme circumstances: male stag beetles fight pugnacious battles over females, by using their extremely large jaws as ferocious weapons. During violent encounters, these jaws have to withstand forces with a wide range of unpredictable directions at several application points. We constructed 1020 finite element models with different input forces to investigate how the male jaws are structurally adapted to avoid failure. The cross-sectional shape of the jaw is adapted to provide robustness against the reaction forces of biting. Nevertheless, the jaw's shape cannot prevent the fact that bite forces induce relatively high material stresses compared to other force directions. Also, males do not confine themselves in combats to bite with the most robust jaw regions. Both observations emphasize the usefulness of bite force modulation to avoid jaw failure. This is likely effectuated by a sensory network in the jaw exoskeleton, as sensor densities are nicely correlated to the maximal material stress caused by 510 different loading directions. Probably, stag beetles use this sensory information to adjust their fighting strategy as well. Finally, male jaws also need to resist the forceful bites inflicted by opponents. Even though this loading applies at other locations along the jaw, and bends the jaw in the opposite direction, our models show that the jaws are equally robust against these external forces as they are against the forces caused by their own biting.